2019
DOI: 10.1002/aur.2138
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between symptoms of autism spectrum disorder and visual impairment among adults with intellectual disability

Abstract: The higher prevalence of autism reported in blind children has been commonly attributed to the confounding effects of an underlying intellectual disability. The aim of this study was to explore the relationship between symptoms of autism and blindness in adults with intellectual disability. We hypothesized that blindness can increase the probability of the autism phenotype, independent of known risk factors, that is, severity of intellectual disability and gender. A general population case register (population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…12 This was in contrast with the larger study reporting more autistic symptoms in adults with intellectual disabilities and visual impairments than in adults with intellectual disabilities but without visual impairments. 16 Adults with autism have been reported to have more blindness or partial sight loss, and deafness or partial hearing loss than other people (12.1% and 17.5%), 6 as have children with autism (3.5% and 2.9%), 7 and people (children and adults combined) with intellectual disabilities compared with other people (13.1% and 12.4%), 3 using the same data from Scotland's Census 2011 as in this current paper. This current study found the comparable rates for people with co-occurring intellectual disabilities and autism for blindness or partial sight loss, and deafness or partial hearing loss was 21.7% and 19.3% for adults, and 16.6% and 10.3% for children.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…12 This was in contrast with the larger study reporting more autistic symptoms in adults with intellectual disabilities and visual impairments than in adults with intellectual disabilities but without visual impairments. 16 Adults with autism have been reported to have more blindness or partial sight loss, and deafness or partial hearing loss than other people (12.1% and 17.5%), 6 as have children with autism (3.5% and 2.9%), 7 and people (children and adults combined) with intellectual disabilities compared with other people (13.1% and 12.4%), 3 using the same data from Scotland's Census 2011 as in this current paper. This current study found the comparable rates for people with co-occurring intellectual disabilities and autism for blindness or partial sight loss, and deafness or partial hearing loss was 21.7% and 19.3% for adults, and 16.6% and 10.3% for children.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…12 An intellectual disabilities register study reported that 95 of the 368 (25.8%) adults with intellectual disabilities who had visual impairment also had markers for autism, compared with 422 of 2674 (16%) of those who had normal vision and that 46 of the 60 (76.7%) of the adults with intellectual disabilities and congenital blindness also had markers for autism compared with only 36 of the 67 (53.7%) with normal vision. 16 We have not identified other papers on sensory impairments or any on physical disabilities in people with co-occurring intellectual disabilities and autism. However, previous large whole population studies that analysed data from the Scotland's Census 2011 have reported that of people with intellectual disabilities, 12.4% reported blindness/sight loss, 13.1% reported deafness/hearing loss and 32.6% reported physical disability.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found a higher prevalence of visual and auditory impairments in children with ASD. Indeed, the associations of both these sensory impairments with ASD were also observed in other studies (Doshi-Velez et al ., 2014; Engelchin-Nissan and Shmueli, 2015; Kiani et al ., 2019). Yet, controversy still exists in the literature regarding the prevalence of hearing impairments in individuals with ASD (Beers et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Learning difficulties due to failure to cater for CVI can thus resemble a primary intellectual deficit (Boot et al, 2012;Flanagan et al, 2003). Several signs can closely resemble a range of neurodevelopmental disorders such as ASD or Attention Deficit Hyperactivity Disorder (ADHD) (Fazzi et al, 2019;Jure et al, 2016;Kiani et al, 2019;Koller, 2012;Mukaddes et al, 2007).…”
Section: Cognitive and Behavioral Consequences Due To CVImentioning
confidence: 99%